Reconciling Civil Code and Customary Law in Chinese Inheritance Disputes in Indonesia - Rahayu, Tajqia Qalbu; Harrieti, Nun (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article examines the settlement of inheritance disputes within the Chinese ethnic community in Indonesia, which faces unique challenges due to legal pluralism. The coexistence of inheritance law under the Indonesian Civil Code and traditional Chinese customary law often leads to conflict, particularly regarding gender equality and fairness in the distribution of assets. This tension reflects a broader issue in harmonizing positive law with deeply rooted cultural traditions.Purposes of the Research: The purpose of this study is to analyze inheritance disputes in the Chinese ethnic community through the perspectives of the Civil Code and Chinese customary law, highlighting points of convergence, areas of conflict, and their implications for legal certainty and justice.Methods of the Research: This study employs a normative juridical method, focusing on legal norms derived from statutory regulations, court decisions, and legal doctrines concerning inheritance law. The primary legal materials analyzed include relevant provisions of the Indonesian Civil Code (KUHPerdata), particularly those regulating heirs and inheritance distribution, as well as Decision Number: 486/Pdt.G/2023/PN Sby of the Surabaya District Court. Secondary materials consist of scholarly books and journal articles on inheritance law, legal pluralism, and Chinese customary law. All materials were collected through document study and analyzed qualitatively using a descriptive-analytical approach.Results of the Research: The findings reveal that Chinese customary law remains patrilineal, tending to prioritize male heirs, whereas the Civil Code upholds equality among heirs regardless of gender or birth order. Judicial decisions increasingly prioritize the Civil Code to ensure justice, indicating a shift away from discriminatory customary practices. This study contributes to the discourse by demonstrating how judicial practice reconciles legal pluralism to guarantee equal protection for all heirs.